A case study on the DMAIC Six Sigma application to prevent injuries in the manufacturing industry. (24th January 2022) - Kenge, Rohit; Khan, Zafar
Ever growing rivalry and non-standard customer requirements triggered a continuous improvement need at goods manufacturing. The injury at workstations to the operators increases the actual lead time of the delivery to the final customer. This paper works on the DMAIC Six Sigma applications to reduce the injury due to burr formation while hammering in the tractor transmission manufacturing. We applied hypothesis testing, DOE, and Z test ANOVA to check the two variables relation with each other and effects of improvement actions over the process at the workstations. We applied cause and effect diagram and matrix, and FMEA that given 15 probable input variables X for the improvement. We applied the improvement actions over these X's and verified the process capability as acceptable. Finally, we reduced total injury from 2 to 0 no's/month against the target of the 0 incidents and RPN reduced from 343 to 96.